Isopathic Use of Auto-Sarcode of DNA as Anti-Miasmatic Homeopathic Medicine and Modulator of Gene Expression? - Teixeira, Marcus Zulian (Homeopathy, 2019)
Introduction In addition to the four pillars of homeopathy, vitalism and the miasmatic theory are often used to explain the health–disease process. According to Hahnemann's concepts, homeopathic miasms are the main obstacle to the cure of chronic diseases, with psora being the fundamental cause of all forms of diseases. According to modern genetics, the disease-promoting epigenetic alterations are the fundamental cause of the manifestation of chronic diseases.Objective This article develops a philosophical–scientific correlation between chronic miasms and disease-promoting epigenetic modifications, aiming to justify the isopathic use of auto-sarcode of an individual's DNA as homeopathic medicine.Results Based on the study of homeopathic doctrine and epigenetics, a conceptual and functional correlation is observed between homeopathic chronic miasms and disease-promoting epigenetic modifications. Additionally, several experimental studies suggest that homeopathy's mechanism of action may be by modulating gene expression.Conclusions By the philosophical–scientific correlations described, it is inferred that disease-promoting epigenetic alterations are the biological representation of the chronic miasms, suggesting the isopathic use of auto-sarcode of DNA as homeopathic therapeutic modulator of gene expression for the management of chronic diseases.
Keywords: homeopathy; miasm; epigenome; isopathy; auto-sarcode of DNA